A Robust Dynamic Positioning Tracking Control Law Mitigating Integral Windup*. Issue 23 (2016) - Kjerstad, Øivind K.; Værnø, Svenn Are T.; Skjetne, Roger
Abstract: This paper deals with the design of a tracking control law for dynamic positioning of marine vessels subject to disturbances. It shows that the integral windup problem can be mitigated by removing the position setpoint in the proportional error term and injecting the velocity setpoint in the integral state. This creates an internal reference point in the control law for the vessel to follow. Control of the transient convergence trajectories is achieved without compromising stability by constraining the internal convergence velocity. The proposed control law provides the same functionality as a conventional tracking control law in combination with a reference filter, but with lower complexity and fewer tuning parameters. A closed-loop simulation case study verifies the theoretical findings and show feasible and robust performance.